P707 Understanding the correlates of STI-HIV co-infections among female sex workers in kitui. (14th July 2019) - Kioko, Japheth; Musimbi, Janet; Bhattacharjee, Parinita; Onyoni, Juddie; Nyakundi, Roselyne; Ndone, Nicholas
Abstract : Background: Genital infections such as Sexually Transmitted Infections (STI) increases the chances of acquiring and transmitting HIV. Kenya AIDS Indicator Survey showed that STI like syphilis was 2.5 times more common among people living with HIV. There is need to understand and respond to such co infections in a HIV prevention Methods: An analysis of cohort data of 1513 Female Sex Workers (FSW) enrolled and receiving HIV services in the KP clinic managed by Hope Word Wide, Kenya in Kitui County was conducted. Cohort data for the period of October 2017 to September 2018 was used and analysed for the STI and HIV screening and diagnosis. The analysis also segregated the analysis by age, above 24 years and below 24 years. Odds Ratio was calculated to measure the association. Results: Out of 1513 FSWs, 1391(92%) received HIV testing services at least once in the year while 1448 (96%) were screened for STI in the same period. A total of 130 (9%) and 29 (2%) FSWs received STI and HIV positive results respectively for the period. The Odds Ratio suggest that those FSWs who have STI had 1.2 times higher chances of being HIV positive. When desegregated by age, FSWs below 24 years with an STI had 2.1 times higher chances. Conclusion: There exists correlation between HIV and STI among Female Sex Workers in Kitui specially among those below 24 years. The intervention needs to screen, diagnose and treat STI among FSWs more aggressively as a response to HIV prevention. Disclosure: No significant relationships.